Transformational Leadership and Educational Innovation - Osias Kit T. Kilag; Marsha H. Malbas; Ma. Kenneth S. Nengasca; Lifejeana Jesusa H. Longakit; Leonora C. Celin; Ronnie Pasigui; Maria Ashley Vannesa N. Valenzona (Journal of Higher Education and Academic Advancement, 2024)
This study explores the relationship between transformational leadership and educational innovation in primary and secondary schools. The study used a qualitative phenomenological research design and conducted in-depth interviews with six school heads in Toledo City Division. The results of the study show that transformational leadership plays a critical role in promoting and supporting educational innovation in schools. Transformational leaders empower teachers and other stakeholders to participate in the implementation of educational innovation initiatives and create a positive and supportive learning environment that fosters growth and development. The findings of this study provide valuable insights for educational leaders, policy makers, and practitioners on the importance of transformational leadership in promoting and supporting educational innovation in schools.